Pengaruh Jumlah Uang Beredar dan Suku Bunga Terhadap Inflasi di Indonesia - Fitri Amaliyah; Aryanto Aryanto (Owner : Riset dan Jurnal Akuntansi, 2022)
Inflation is an increase in the price of an item that tends to be continous. This study aims to find out the effect of the money supply and interest rates on inflation in Indonesia for the period 2015-2020. The data in this study is secondary data obtained from the website while analysis data uses WarpPLS (Descriptive quantitative, outer model, inner model, hypothesis test). Based on the result of hypothesis testing with WarpPLS showed that the variable amount of money supply negatively and significanly on inflation indicated by the path coefficient value of -0,723 and pvalue 0,001. In variable interest rates have a positive and insignificant effect on inflation indicated by the path coefficient values 0,169 and pvalue 0,085. Related to the results of the analysis, this could be due to the fact that the policies and strategies implemented by the government were still in an ineffective condition to suppress existing inflation, so the government had to be more relevant in making policies so that inflation did not continue to decline and instead became a deficit which had an impact on the stability of the economy in Indonesia. The government needs to implement monetary policy carefully so that the economy in Indonesia is stable.